Modeling the incoherent scatter radar spectrum perpendicular to the Earth's magnetic field - Milla, Marco (2008)
Diapositivas presentadas en: ISEA 12 - 12th International Symposium on Equatorial Aeronomy, May 18-24, 2008. Crete, Greece.